Myślenie wizualne w UX na przykładzie sztuki ulicznej - Jabłońska, Jagoda (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
With the development of research on the functioning of cognitive processes and communication, it is possible to search for further relationships between these fields. The article “Visual thinking in UX on the example of street art” is empirical in character. It presents visual thinking as a tool for designing the experience of a user of specific information. The indicated notions were applied to paintings on the walls, which are an element of street art. The purpose is to learn the way of thinking of users of their information and check how they decode the message designed by the sender. The basis for the article are the materials collected from Polish and foreign sources and the results of the eye tracking study carried out in June 2022 at the Laboratory of Cognition and Communication, which is part of the Interactive Centre for Communication and Social Studies of the University of Szczecin.